Researcher Profile: An Interview with D. Bruce Ross - D. Bruce Ross (Journal of Financial Therapy, 2018)
D. Bruce Ross, Ph.D., is an Assistant Professor in the Family Sciences Department at the University of Kentucky. He has a Master’s in Marriage and Family Therapy, and a Ph.D. in Human Development and Family Science with an Emphasis in Marriage and Family Therapy and a specialization in financial counseling and financial therapy practices. Dr. Ross’ professional and research interests primarily focus on personal and family financial well-being. At the University of Kentucky, he is currently helping to develop a new undergraduate program of Consumer Economics and Personal Finance within the Family Sciences Department. Also, Dr. Ross is the current Treasurer of the Financial Therapy Association, where he also sits on the Regulatory Committee, Conference Planning Committee, and Chairs the Business Development Committee.
Keywords: research; faculty; financial therapy; marriage and family therapy; family financial well-being